Maternal variants within the apolipoprotein L1 gene are associated with preeclampsia in a South African cohort of African ancestry. (March 2020) - Thakoordeen-Reddy, Semone; Winkler, Cheryl; Moodley, Jagidesa; David, Victor; Binns-Roemer, Elizabeth; Ramsuran, Veron; Naicker, Thajasvarie
Highlights: Maternal APOL1 G1 contributes to early-onset preeclampsia in South African women. There is a 2-fold increased risk of PE in women carrying at least one G1 allele. This may be used a screening tool in clinical practice. Abstract: Objective: Preeclampsia (PE) is a complex pregnancy-specific medical disorder arising from an ischaemic placenta releasing factors causing widespread endothelial damage involving multiple organs systems, such as the renal system. Two variant alleles, termed G1 and G2, of the APOL1 gene are strongly associated with progressive renal disease and preeclampsia in the recessive or compound heterozygous state. Hence, we investigated the role of maternal APOL1 genotype in the pathogenesis of preeclampsia in South African women of African ancestry. Study design: This case-control study comprised three groups of South African pregnant women of African ancestry attending a regional hospital in Durban, South Africa: mothers experiencing normotensive pregnancies, early onset preeclampsia and late onset preeclampsia underwent APOL1 genotyping. Differences in G1 and G2 allele and genotype frequencies were analysed for the three groups. Results: Our study revealed a significant association between the maternal A POL1 G1 risk allele and early-onset PE development (OR 2.2, p = 0.03). Among the EOPE group, 5 % [OR(95 %CI) 0.94 (0.29–3.12)] of the study population carried two risk alleles, 49 % [OR(95 %CI) 1.34 (0.77–2.3)] carried at least one risk allele, while 46 % of the participants did not carry either risk allele, compared to the normotensive pregnant group, where 52 % carried no risk allele, 42 % had at least one risk allele and 6 % of the women had both risk alleles. Conclusion: Our results suggest that maternal APOL1 G1 risk allele may contribute to the development of early-onset PE in South African pregnant women of African ancestry either directly or by transmission of a APOL1 risk allele to the foetus.